Effects of salinity and plant-based diet or animal-plant combination diet on the performance and metabolic status of juvenile Nile tilapia - Rafaela Mocochinski Gonçalves; Marlise Teresinha Mauerwerk; Izabel Volkweis Zadinelo; Sergio Rodrigo Fernandes; Ricardo Fiori Zara; Lilian Dena Santos (Semina: Ciências Agrárias, 2022)
The purpose of this study was to evaluate the effects of salinity and plant-based diet or animal-plant combination diet on the performance and metabolic status of juvenile Nile tilapia (Oreochromis niloticus). The experimental design was completely randomized in a 4 × 2 factorial scheme with four replicates. The treatments were established by the combination of salinities of 0, 10, 20, and 30 g L-1 with an animal-plant combination diet (AP) or plant-based diet (P). The replicates were 60 L tanks with 12 fish per tank. Diets were provided for 32 days, and the fish were fed three times a day (8, 12, and 17 h) until apparent satiety. Daily feed intake (DFI) was measured, body weight (BW) was recorded at the beginning and end of the trial, and total length (TL) and standard length (SL) were measured at the end of the trial. Average daily gain (ADG), specific growth rate (SGR), feed conversion ratio (FCR), and survival rate were calculated. After the biometric measurements were made at the end of the trial, blood samples were collected to determine the plasma concentrations of total protein (TP), glucose, cholesterol, and triglycerides (TG). The fish were euthanized, and the hepatopancreas was collected and weighed; thereafter, the hepatosomatic index (HSI) was calculated. An interaction was detected between salinity and diet type for final BW, ADG, TL, and SL. These traits were not influenced by salinity when it was associated with the AP diet, but reduced linearly with salinity in the P diet. DFI and survival rate were independently affected by salinity: DFI reduced linearly with salinity levels and survival rate was higher at a salinity of 10 g L-1. HSI increased linearly with salinity levels and was lower in the P diet than in the AP diet. Salinity had a quadratic effect on plasma TP, and the maximum value for this metabolite (2.96 g dL-1) is attained at a salinity of 10.26 g L-1. There was an independent effect of diet on the plasma concentrations of cholesterol and TG, which were lower in the P diet than in the AP diet. The salinity of 10 g L-1 associated with diet composed of animal and plant ingredients led to a better performance, higher survival rate, and less stressful environmental conditions for juvenile Nile tilapia.